NARP syndrome in a patient harbouring an insertion in the MT-ATP6 gene that results in a truncated protein. Issue 1 (5th January 2009) - López-Gallardo, E; Solano, A; Herrero-Martín, M D; Martínez-Romero, Í; Castaño-Pérez, M D; Andreu, A L; Herrera, A; López-Pérez, M J; Ruiz-Pesini, E; Montoya, J
Abstract : Background: Neurogenic muscle weakness, ataxia and retinitis pigmentosa (NARP) syndrome have been associated to m.8993T>G/C mutations in the subunit 6 of the ATP synthase (p.MT-ATP6). Methods: We have performed a mutational screening of the mitochondrial DNA gene encoding for this protein in 62 patients with the disease, that do not carry any of the common mutations described to date. Results: We report clinical and molecular data in one patient who harbours a de novo insertion in the MT-ATP6 gene that results in a truncated subunit. The mutation was heteroplasmic (85%) in muscle DNA and the BN-PAGE analysis showed a clear decrease in the amount of ATP synthase. Conclusion: Molecular analysis of NARP patients cannot be limited to the search of the m.8993T>G/C and either the ATP6 or the whole mtDNA should be sequenced.